2020
DOI: 10.1158/1541-7786.mcr-20-0091
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Patient-Derived Mesenchymal Stromal Cells to TGFB1 Supports Fibrosis Induction in a Pediatric Acute Megakaryoblastic Leukemia Model

Abstract: Bone marrow fibrosis (BMF) is a rare complication in acute leukemia. In pediatrics, it predominantly occurs in acute megakaryoblastic leukemia (AMKL) and especially in patients with trisomy 21, called myeloid leukemia in Down syndrome (ML-DS). Defects in mesenchymal stromal cells (MSC) and cytokines specifically released by the myeloid blasts are thought to be the main drivers of fibrosis in the bone marrow niche (BMN). To model the BMN of pediatric patients with AMKL in mice, we first established MSCs from pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The BMM in children with Down syndrome (DS)-acute megakaryoblastic leukemia (AMKL) is characterized by marrow fibrosis [ 138 , 139 ], and TGF-β has been revealed as the main mediator of bone marrow fibrosis [ 140 ]. Based on pediatric patient-derived samples, Hack et al showed that TGF-β supports fibrosis and thus significantly contributes to leukemogenesis in pediatric DS-AMKL [ 141 ].…”
Section: Dysregulated Leukemic Bone Marrow Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The BMM in children with Down syndrome (DS)-acute megakaryoblastic leukemia (AMKL) is characterized by marrow fibrosis [ 138 , 139 ], and TGF-β has been revealed as the main mediator of bone marrow fibrosis [ 140 ]. Based on pediatric patient-derived samples, Hack et al showed that TGF-β supports fibrosis and thus significantly contributes to leukemogenesis in pediatric DS-AMKL [ 141 ].…”
Section: Dysregulated Leukemic Bone Marrow Microenvironmentmentioning
confidence: 99%
“…Given that MKs and leukemic blasts abundantly express TGF-β, resulting in markedly increased TGF-β levels in the DS-AMKL BMM, and TGF-β has been shown to induce early-stage marrow fibrosis in DS-AMKL [ 141 ], TGF-β appears to play a pivotal role in the leukemogenesis of AMKL (FAB-M7) in children with and without trisomy-21. Exosomes released in AML have been revealed to contain high concentrations of TGF-β and to impact leukemogenesis and the therapeutic response [ 134 , 142 ].…”
Section: Dysregulated Leukemic Bone Marrow Microenvironmentmentioning
confidence: 99%